Study protocol of the Hungarian Longitudinal Study of Healthy Brain Aging (HuBA). - Bankó Éva Mária (IDEGGYOGYASZATI SZEMLE / CLINICAL NEUROSCIENCE, 2024)
Neurocognitive aging and the associated brain diseases impose a major social and economic burden. Therefore, substantial efforts have been put into revealing the lifestyle, the neurobiological and the genetic underpinnings of healthy neurocognitive aging. However, these studies take place almost exclusively in a limited number of highly-developed countries. Thus, it is an important open question to what extent their findings may generalize to neurocognitive aging in other, not yet investigated regions. The purpose of the Hungarian Longitudinal Study of Healthy Brain Aging (HuBA) is to collect multi-modal longitudinal data on healthy neurocognitive aging to address the data gap in this field in Central and Eastern Europe..We adapted the Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging study protocol to local circumstances and collected demographic, lifestyle, mental and physical health, medication and medical history related information as well as recorded a series of magnetic resonance imaging (MRI) data. In addition, participants were also offered to participate in the collection of blood samples to assess circulating inflammatory biomarkers as well as a sleep study aimed at evaluating the general sleep quality based on multi-day collection of subjective sleep questionnaires and whole-night electroencephalographic (EEG) data..Baseline data collection has already been accomplished for more than a hundred participants and data collection in the secondsession is on the way. The collected data might reveal specific local trends or could also indicate the generalizability of previous findings. Moreover, as the HuBA protocol also offers a sleep study designed for thorough characterization of participants’ sleep quality and related factors, our extended multi-modal dataset might provide a base for incorporating these measures into healthy and clinical aging research. .Besides its straightforward national benefits in terms of health expenditure, we hope that this Hungarian initiative could provide results valid for the whole Central and Eastern European region and could also promote aging and Alzheimer’s disease research in these countries..